2015
DOI: 10.1093/qjmed/hcv104
|View full text |Cite
|
Sign up to set email alerts
|

Decreased risk of intracerebral hemorrhage among patients with milder allergic rhinitis

Abstract: This study showed for the first time that milder AR is correlated with a reduction in the risk of ICH, particularly for elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…AR), thus they are more often diagnosed with AR. A recent study reported that milder AR correlates with a reduction in the risk of intracranial hemorrhage [ 20 ]. Mediating effects of medical utilization on the association with AR might be attenuated for central obesity due to the difficulty of managing the disease [ 21 ] and for dyslipidemia because it is likely to be clinically overlooked [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…AR), thus they are more often diagnosed with AR. A recent study reported that milder AR correlates with a reduction in the risk of intracranial hemorrhage [ 20 ]. Mediating effects of medical utilization on the association with AR might be attenuated for central obesity due to the difficulty of managing the disease [ 21 ] and for dyslipidemia because it is likely to be clinically overlooked [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used the Longitudinal Health Insurance Database (LHID), which consists of 1 million patient data from 1996 to 2000 that were extracted from the catalogue of beneficiaries in the National Health Insurance Research Database (NHIRD). 26 , 28 The NHIRD, which comprises >98% of the population of Taiwan, was established on the basis of the NHI program implemented in 1995. The contents of the LHID include information on patients’ medical registry facilities, their demographic data, and the types of medical care they underwent.…”
Section: Methodsmentioning
confidence: 99%
“… 20 22 As reported in previous investigations, type 1 T helper cells (Th1), which are primarily responsible for cellular immunity and enhance the secretion of proinflammatory cytokines, and type 2 T helper cells (Th2), which are responsible for humoral immunity and modulate the functions of Th1, both play a critical role in the immune responses of PID induced by C trachomatis and N gonorrhoeae . 23 25 Tseng et al 26 found that a milder form of allergic rhinitis (AR), a Th2-modulated inflammatory disorder, could reduce the risk of ICH, and in an investigation with a short follow-up period (2004–2005), 27 Chen et al found an increased risk of ischemic stroke among patients with PID. However, whether PID, a disease involving the immune response of both Th1 and Th2 cells, advances or attenuates the development of ICH remains unclear.…”
Section: Introductionmentioning
confidence: 99%